Combination of Intraoperative Magnetic Resonance Imaging and Intraoperative Fluorescence to Enhance the Resection of Contrast Enhancing Gliomas. Issue 1 (23rd March 2015) - Gessler, Florian; Forster, Marie-Thérèse; Duetzmann, Stephan; Mittelbronn, Michel; Hattingen, Elke; Franz, Kea; Seifert, Volker; Senft, Christian
Abstract: BACKGROUND: Evidence suggests that extent of resection (EOR) is a prognostic factor for patients harboring gliomas. Recent studies have displayed the importance of intraoperative magnetic resonance imaging (iMRI) with 5-aminolevulinic acid (5-ALA) fluorescence-guidance in order to maximize EOR. OBJECTIVE: To compare iMRI and 5-ALA fluorescence-guidance and the impact on patient survival. METHODS: Thirty-two patients with contrast-enhancing gliomas undergoing intended gross total resection (GTR) were included in a prospective study. Surgeries were started under white-light conditions. When GTR was thought to be achieved, an iMRI scan was performed and a blue light turned on to search for unintentionally remaining tumor tissue. iMRI findings were compared with intraoperative fluorescence findings. Histological examination of tumor bulk and any additionally resected tissue was performed. All patients underwent early postoperative high-field MRI to determine EOR. RESULTS: In 13 patients (40.6%), iMRI and fluorescence unequivocally did not show residual tumor intraoperatively. In 19 patients (59.4%), resection was continued due to iMRI or fluorescence findings. In 9 of these (47.4%), iMRI and fluorescence findings were inconsistent regarding residual tumor. GTR according to postoperative MRI was achieved in all but 1 patient. Histological examination ruled out false positive findings in all additionally resected specimens. Sensitivity and specificity to detect residual tumor tissue were 75% and 100%, respectively, for iMRI and 70% and 100% for 5-ALA fluorescence. CONCLUSION: Use of iMRI as well as fluorescence-guidance are appropriate methods to improve the extent of resection in surgery of contrast-enhancing gliomas. Best results can be achieved by complementary use of both modalities.